CAPABILITY OF SEA CUCUMBER Holothuria scabra TO REMOVE NITROGEN AND PHOSPHOR WASTE FROM SHRIMP PONDS CULTURE - Supriyono, Eddy; Nirmala, Kukuh; Sabilu, Kadir; Wa Iba, Wa Iba; Sabilu, Murni (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
Solid organic waste (PSW) in shrimp ponds contains relatively high levels of nitrogen and phosphorus and can endanger the ecological balance of the waters. This study evaluates the ability of sea cucumber Holothuria scabra to remove nitrogen and phosphorus loads from shrimp pond sediment waste in water and sediment. Sea cucumbers were reared for 40 days with a density of 20 individuals/m2 (average body weight 2.65±0.09 g) and a double-bottom recirculation system. Five levels of PSW accumulation were inserted into the aquarium substrate and were the sole source of nutrition for sea cucumbers without additional feeding: 10%, 20%, 30%, 40%, and 50% (with three replications). The results showed that increasing the PSW content in the aquarium research substrate significantly increased the substrate's TOC, TN, and TP content and increased the concentrations of TOM, DOC, NH3, NO2, and PO4 in the water column. The activity of sea cucumbers in utilizing PSW nutrients in all treatments up to a PSW level of 50% significantly reduced TOC, TN, and TP in sediments. This activity also substantially removes the concentration of TOM, DOC, NH3, NO2, and PO4 in the water. It is estimated that every kilogram of H. scabra can remove up to 12.65-12.73 g of nitrogen/day and 2.57-2.60 g of phosphorus/day contained in the solid organic waste of shrimp ponds. Therefore, this study concluded that H. scabra has great potential to be used as integrated multi-trophic aquaculture (IMTA) species, especially to remove nitrogen and phosphorus loads from shrimp pond sediment waste in waters.